A STUDY OF STUDENTS’ RELUCTANCE TO SPEAK AT ENGLISH DEPARTMENT OF UNIDAYAN - Nety Nety (English Education Department, 2022)
The problem of the research was “what factors did affect students’ reluctance to speak in Speaking class?” the objective of this research was to know what factors did affect students reluctant to speak in Speaking class. The research was a descriptive qualitative research. The subject of the research were students and a lecturer of Speaking subject in English Department of Unidayan. The data of research were collected through observatin, interview and documentation. The data were analyzed through three steps adopted from Miles and Huberman; data reduction, data display and conclusion drawing. The result of this research showed that students’ reluctance to speak in speaking class caused by two factors namely linguistic problems which were lack of vocabulary, grammar and pronounciation. And non linguistic problem which were lack of self confidence, shyness, nervous, shaking, and worried in making mistake. In addition, students also did not gain any additional English courses outside their class.